Keratin/chitosan as novel grafts for peripheral nerve regeneration - Carvalho, C. R. (2014)
For many years Peripheral Nerve Injuries (PNI) has been raising major concerns in regenerative medicine. Currently, the gold standard treatment for PNI is the autologous nerve grafting but it presents several drawbacks. Chitosan, along with keratin [1], for their good biocompatibility and physicochemical properties have been widely used as biomaterials in tissue engineering scaffolding. Many engineered biomaterials, natural or synthetic, have also been studied, but its poor architecture and lack of appropriate biological cues have been limiting nerve tissue regeneration [2]. In this study, an innovative combination of chitosan and keratin is obtained in order to create a novel nerve conduit (medical device) aimed at finding applications in the treatment of PNI.